Characterization of an OrtT-like toxin of Salmonella enterica serovar Houten - Bertucci Barbosa, Luiz Carlos; Carrijo, Rodolfo dos Santos [UNESP]; Conceicao, Milena Barbosa da [UNESP]; Maimoni Campanella, Jonatas Erick [UNESP]; Junior, Edson Crusca [UNESP]; Secches, Thais Oliveira; Bertolini, Maria Celia [UNESP]; Marchetto, Reinaldo [UNESP] (Springer, 2019)
The Escherichia coli GhoT/GhoS system is a type V toxin-antitoxin system in which the antitoxin GhoS cleaves the GhoT mRNA, controlling its translation. GhoT is a small hydrophobic protein that damages bacterial membranes. OrtT is a GhoT-like toxin, but it apparently lacks a corresponding antitoxin and serves a different physiologic role. Using a profile hidden Markov model approach, a Salmonella enterica serovar Houten genome was screened to obtain homologs of GhoT/OrtT. We only found one protein (referred to here as OrtT-Sal) that shared more sequence identity with OrtT than GhoT. The chromosomal region around the coding sequence of OrtT-Sal suggests that it is an orphan toxin and can be under RpoH activation. To study OrtT-Sal, we chemically synthesized and expressed in E. coli the whole toxin and its N- and C-terminal regions (OrtT-Sal(1-29) and OrtT-Sal(29-57), respectively). Our findings have shown that the overproduction of the polypeptides resulted in severe growth inhibition and cell lysis. Using circular dichroism, we found that OrtT-Sal, OrtT-Sal(1-29), and OrtT-Sal(29-57) form an alpha-helical structure in the presence of SDS micelles or TFE. Finally, using carboxyfluorescein-loaded lipid vesicles, we determined that the polypeptides damage lipid membrane directly.
Keywords: Toxin-antitoxin system; OrtT; GhoT; Orphan toxin